Rebuilding local seed system of native crops in earthquake affected areas of Nepal, Proceedings of a National Sharingshop 18 Dec 2017, Kathmandu - Joshi, B.K.; Gauchan, D. (NAGRC, 2017)
The main aim of the project is to revive and strengthen local seed system capacity and resilience of households through rescue collection, conservation, multiplication and repatriation of native and threatened crop seeds in the most severely affected 10 districts of central and western Nepal, where farmers’ traditional seed stocks have been completely destroyed by devastating earthquakes that occurred in April and May 2015. This project is being implemented by Bioversity International in partnership with the National Gene Bank of Nepal and Local Initiatives for Biodiversity Research and Development (LI-BIRD). The project is funded by two different sources. The first funding source came from GRPI-2 Project of the Bioversity International through the Netherlands Government ‘Strengthening National Capacities to implement the International Treaty on Plant Genetic Resources for Food and Agriculture (ITPGRFA)’ implemented by LI-BIRD in three districts (Sindhuplanchowk, Dolakha and Ramechhap). The second funding came through Global Crop Diversity Trust (GCDT) in 7 affected districts (Gorkha, Lamjung, Dhading, Nuwakot, Makawanpur, Kavre, Rasuwa,) led by National Genebank of Nepal. The project started in June 2015 and to be completed in December 2017.